0 - Editorial Samir Amin (1931-2018): A Titan has Gone Home to Rest - Murunga, Godwin (CODESRIA Bulletin, 2021)
The Council for the Development of Social Science Research in Africa (CODESRIA) learned with immense shock and sadness of the passing on of Professor Samir Amin on Sunday, 12th August 2018. Subsequently, Prof. Samir Amin’s body was interned at Père Lachaise in Paris on 1st September 2018 at a site provided by the French Communist Party. The Council was represented at the burial by Prof. Fatow Sow and Dr. Cherif Sy; two members of the CODESRIA community who have worked with Samir Amin for a while. For CODESRIA, this marks nothing less than the end of an era in the history of African social research given the many pioneering roles the late Professor Amin played as a scholar, teacher, mentor, friend, and revolutionary. Samir was many things to us as a Council; for the younger members of the community, it meant much more to be in his company at the numerous CODESRIA meeting he attended. A model for three generations of African and, indeed, radical scholars globally, Samir was that giant Baobab tree whose grandeur of intellect and spirit made him a worthy role model. While serving as Director of the United Nations African Institute for Economic Development and Planning (IDEP), he hosted the initial scaffolding of the CODESRIA at IDEP, brought together and nurtured new talent that laid the foundations which launched Council on a path of growth and resilience to what it is to-date. As the final note on his reflections contained in this Bulletin illustrates, while serving as CODESRIA’s founding Executive Secretary, Samir worked very closely with Abdalla Bujra and later Thandika Mkandawire, to shape the initial years of CODESRIA’s intellectual identity and trajectory. After CODESRIA relocated from the premises of IDEP to a new home in the Fann Residence part of Dakar, Samir Amin remained engaged with Council and its community of scholars, participating actively and effectively in all its activities. This 15th General Assembly of CODESRIA is perhaps the first Assembly without Samir Amin presence. In all previous General Assemblies, Samir has been a notable presence even giving the Cheikh Anta Diop Lecture at the 10 Assembly in Kampala, Uganda. It is at the General Assembly that many young academics interacted with Samir, often for the first time and indeed experiencing the awe of his presence. Though Samir is absent at the current Assembly, there is no doubt that his intellectual and revolutionary spirit is definitely present just as the thoughts and ideas that he shared so generously and to the very end will continue to inspire reflection and debate. Samir Amin’s intellectual journey was a long and illustrious one. It was a journey marked by commitments that distinguished him as a scholar of unparalleled convictions. He died still an unapologetic socialist academic or, as the title of his memoir reads, ‘an independent Marxist’ whose work was driven by an unshakeable conviction to confront and oppose totalizing economic orthodoxies. He treated this confrontation and opposition as a prelude to social transformation. He was steadfast in his belief that the world must shift away from capitalism and strive to build new ‘post-capitalist’ societies. He described capitalism as a small bracket in the long history of human civilization. His works identify and record the multiple crises of capitalism, a system he described as senile and obsolete. In its place, Samir Amin formulated a political alternative that he envisioned would proceed by i) socializing the ownership of monopolies, ii). definancializing the management of the economy and iii) deglobalising international relations [cited in Campbell, 2015: 286]. For him, these three directions provided the basis of an active politics of dismantling capitalism; a politics he committed his skill and energy mobilizing for. Even as he grew older, he mustered fresh bursts of energy to continue the struggle and to the very last days when he was in Dakar, he was apart of the team of scholar/ activists gathered together by International ENDA Third World Network to draft the Alternative Report on Africa (Dakar, 2018). CODESRIA was apart of this process and the Report will by shared at this General Assembly. Many of Samir Amin’s writings make the point repeatedly on the urgent necessity to dismantle the ‘obsolete system’ known as capitalism. However, none was as emphatic in rethinking the underlying cultural underpinning of the ‘obsolete system’ like Eurocentricism. In that engaging publication, he provided a rggesounding critique of world history as is centered around Eurocentric modernity and invites us to understand modernity as an incomplete process that, to survive its current crises, will need ‘economic, social and political reconstruction of all societies in the world.’ Embedded in this argument is a long held position about the importance of the Bandung moment (1955) as a moment of an alternative globalization based on Afro-Asian solidarity. It is from this perspective that one understands why Samir Amin emphasized the importance of China [see tribute by Sit Tsui and Yan Xiaohui in this bulletin]. Afro-Asian solidarity was the basis upon which Samir Amin located his alternative politics which also defined his towering global outlook and presence. There is no doubt that Samir Amin’s intellectual presence was defined by depth of knowledge, complexity of thought and fidelity to Marxist organising principles. There is no way of summarizing the corpus of work he produced, the revolutionary engagements he undertook and the transformative potential that led him to remain steadfast even when many others were only too happy to find a good reason to backtrack and conform. His work is enormous in volume but also in the depth of its knowledge and relevance to society. He provoked and joined debates across the globe but more importantly with comrades in Latin America and Asia, those of the dependency and underdevelopment school but also later from a South-South perspective. In CODESRIA’s flagship journal Africa Development alone, Samir Amin published twenty articles. A biodata document he shared with the Council has 24 books in English and 41 in French. He is published in English, French, Arabic, Italian, Portuguese, and Spanish to name but these few languages. In all these publications and in the various languages, Samir Amin articulated his belief in alternatives, and as indicated above, this belief remained strong even to the last month of his life on earth. Born to an Egyptian father and French mother on 3rd September 1931 in Cairo, Egypt, Samir Amin’s convictions owe much to the context of his childhood all the way from Port Said in northern Egypt to Cairo where he schooled. He spent his early life in Egypt where he attended his formative schooling before proceeding to France to pursue higher education at Institut d’Etudes Politiques de Paris (“Sciences Po”). Here, he earned a diploma in 1952 and later a PhD in 1957 at the Sorbonne. Samir later earned another diploma in mathematical statistics from L’institut national de la statistique et des etudes economiques. He had always been interested in radical thought and action from early on, noting in an interview that he already considered himself a communist in Secondary School. Even though he and his cohort did not know what communism really meant in their early childhood, they assumed it meant “equality between human beings and between nations, and it meant that this has been done by the Russian revolution.” It is not surprising that with this pedigree, Samir Amin focused in his graduate research on “The origins of underdevelopment – capitalist accumulation on a world scale” and emphasized in his work that underdevelopment in the periphery was, in large measure, due to the working of the capitalist system. He consequently underscored the need to search for socialist alternatives to liberal globalisation. Samir Amin returned to Cairo in 1957, worked briefly in Gamal Abdel Nasser’s Institute for Economic Management (1957–1960) before heading to work as an adviser in the Ministry of Planning in Mali (1960- 1963). Subsequently, Samir Amin’s intellectual life became largely internationalist in orientation, and anchored principally on the question of accumulation as key to understanding underdevelopment. He maintained the sojourn between France where he took up a Professorship in 1966 and Dakar, Senegal his adopted home where he worked for ten years, from 1970 to 1980 at IDEP. Later in 1980, he founded the Third World Forum, originally hosted at the CODESRIA Secretariat, and lent his considerable weight to the institutionalisation of ENDA and the World Forum for Alternatives. His support for revolutionary politics is marked not just in the books and papers he published but also in the lecture circuit where he spoke to audiences about the undeniable relevance of radical politics. Samir Amin’s thinking was in large measure defined by the solidarity built around the Bandung Confer- ence of 1955. This remained a critical touchstone in his work in which non-western civilisations and his- tories played an important role. Bandung, for him, inaugurated a different pattern of globalisation, the one he called ‘negotiated globalisation.’ Though not asufficientbasisforcomplete“de-linking”from‘ob- solescent capitalism’, Samir Amin saw in Afro-Asian solidarity possibilities and pathways to that delinking; the process, as he explained, by which you submit “ex- ternal relations to the needs of internal progressive so- cial changes and targets.” The notion of ‘delinking’ oc- cupied a major place in Samir Amin’s thinking and is positioned in contrast to ‘adjustment’ that was the pre- ferred approach of the Bretton Woods Institutions. As Mamdani shows elsewhere in this Bulletin, there are major problematic elements of this notion that Samir Amin continued to grapple with. But ultimately, Samir Amin noted that delinking is in fact a process that, de- pending on the societies implementing it, can be used to install graduated level of autonomous development instead of countries in the periphery remaining locked into and merely adjusting to the trends set by a funda- mentally unequal capitalist system. In Samir Amin, we found the true meaning of praxis; a thinker who insisted that his work has immediate relevance to society. His departure deprives us of the practical energy he brought to our meetings and debates; and denies radical thinkers a model around whom they found the compass that enabled them to navigate the treacherous, indeed murderous, waters of capitalism. We however are lucky to have lived in his company, to have learned from his fountain of knowledge and to have shared in the passion of his convictions. The Council plans to invigorate the value of his legacy by celebrating him during this 15th General Assembly but also beyond the confines of the Assembly. Thus, this edition of the Bulletin contains two intertwined sets of essays; all organised around Samir Amin. In the one instance, we have a selection of messages in his memory. One the other, we have a selection of essays he authored. Separately, we will re-publish all the essays he published in Africa Development in a special issue of the journal to provide them in one collection for posterity. But whichever way, and as his own reflection in the essay published in this volume and his memoirs show, CODESRIA is an inheritance that Samir Amin bequeathed the African social science community. As such, it is fitting that the Bulletin designed for the 15th CODESRIA General Assembly is also a Bulletin that publishes essays in his honour. The choice of theme for the General Assembly predates the passing on of Samir Amin. But the theme itself is one that was dear to Samir Amin. It is our pleasure therefore to present the essays contained here as essays that shed light on a life lived fully but also that open up a space to explore the unfulfilled promises of globalisation. We hope that at the end of it, this will be a fitting study in honour of our departed icon but also a commentary on the key issues the 15th General Assembly explored.